2018
DOI: 10.1038/nature26156
|View full text |Cite
|
Sign up to set email alerts
|

Modular assembly of the nucleolar pre-60S ribosomal subunit

Abstract: Early co-transcriptional events during eukaryotic ribosome assembly result in the formation of precursors of the small (40S) and large (60S) ribosomal subunits1. A multitude of transient assembly factors regulate and chaperone the systematic folding of preribosomal RNA subdomains. However, owing to a lack of structural information, the role of these factors during early nucleolar 60S assembly is not fully understood. Here we report cryo-electron microscopy (cryo-EM) reconstructions of the nucleolar pre-60S rib… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
165
1
6

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
2
2

Relationship

2
5

Authors

Journals

citations
Cited by 137 publications
(190 citation statements)
references
References 35 publications
13
165
1
6
Order By: Relevance
“…In vivo crosslinking studies of Rrp5 have shown its proximity to several sites on the pre-rRNA, including the central domain of the 18S, ITS1 and domain II of the 25S, consistent with our data (Lebaron et al 2013). Domain II also leads to the association of several factors completing the ring structure around domain I and II which was described in the nucleolar pre-60S structure (Sanghai et al 2018), composed of Nsa1, Rpf1, Mak16, Rrp1, and the already associated Brx1 and Ebp2.…”
Section: Resultssupporting
confidence: 90%
See 2 more Smart Citations
“…In vivo crosslinking studies of Rrp5 have shown its proximity to several sites on the pre-rRNA, including the central domain of the 18S, ITS1 and domain II of the 25S, consistent with our data (Lebaron et al 2013). Domain II also leads to the association of several factors completing the ring structure around domain I and II which was described in the nucleolar pre-60S structure (Sanghai et al 2018), composed of Nsa1, Rpf1, Mak16, Rrp1, and the already associated Brx1 and Ebp2.…”
Section: Resultssupporting
confidence: 90%
“…Fig. 2) (Kater et al 2017;Sanghai et al 2018;Zhou et al 2018). Completion of domain VI induces the incorporation of almost 20 ribosome assembly factors, the 5S rRNA and association of snR10.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our data for the wild type Has1 are in a very good agreement with the recently published PAR-CRAC analysis (19). The observed crosslinking sites in the 5.8S/25S region also coincide well with the location of Has1 in several recent cryoEM structures of pre-60S ribosomes (27)(28)(29). The binding sites of the wild type Has1 in the 18S/ITS1 region are in close proximity to the binding sites of the pre-40S assembly factors Enp1, Ltv1 and Tsr1 (22).…”
Section: Discussionsupporting
confidence: 91%
“…Can Has1 function as a dimer? Has1 was observed to self-interact in the yeast two-hybrid assays (36,37).On the other hand, Has1 identified in the cryoEM structures of pre-60S ribosomes is present as a monomer (27)(28)(29). It is possible that Has1 is recruited as dimer but then separates and each monomer functions separately in the pre-40S and pre-60S pathways.…”
Section: Discussionmentioning
confidence: 99%